SURVEI KEPUASAN PESERTA DIDIK SEKOLAH DASAR SEGUGUS 5 PENGASIH TERHADAP PROGRAM MAKAN BERGIZI GRATIS (MBG) - Hendra Saputra Wibowo; Afifah Siska Febriani; Novi Trisnani (CV. Adiba Aisha Amira, 2026)
The Free Nutritious Meal Program (MBG) is one of the government’s efforts to improve the nutritional status and learning quality of elementary school students. This study aims to analyze students’ satisfaction levels with the implementation of the MBG program in five elementary schools within Cluster 5 of Pengasih District. The research employed a quantitative method using questionnaires as the primary data source and supplementary secondary data obtained through interviews. The study involved 219 students from a total population of 481, determined using the Slovin formula with a margin of error of 0.5%. Data analysis referred to the SERVQUAL dimensions, including Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The results showed that the overall satisfaction level ranged between 7.50 and 8.04, categorized as “good to very good.” The Tangibles dimension obtained the highest mean score (8.04), indicating that students were satisfied with the cleanliness, appearance, and presentation of meals. However, the Assurance dimension received the lowest score (7.50), suggesting the need for improvement in food safety and quality aspects. Overall, the MBG program was considered effective in supporting students’ health, learning motivation, and overall well-being within the elementary school environment